Comparison of the Effectiveness of Life Therapy and Acceptance and Commitment Therapy on Mental Pain and Zest for Life in Patients with Leukemia - Ghoreishiseyedmahaleh, Seyedehsaeideh; Hassanzadeh, Ramezan; Norouzi, Asghar (KMAN Counseling & Psychology Nexus, 2024)
Cancer is one of the leading causes of disorders, mortality, and disability worldwide and represents a prevalent and increasing disease that demands a significant portion of healthcare efforts. Consequently, this study examines and compares the effectiveness of life therapy and acceptance and commitment therapy on mental pain and zest for life in patients with leukemia. The present study is experimental. The statistical population included all male patients who visited Imam Hospital in Sari in 2023 and had received a confirmed diagnosis of leukemia. From this population, 45 patients with leukemia were selected through non-random convenience sampling and randomly assigned to two experimental groups (life therapy and acceptance and commitment therapy) and one control group (15 participants in each group) using simple random allocation. Data were collected using the Orbach and Mikulincer Mental Pain Questionnaire (OMMP) and the Zest for Life Questionnaire by Hassan Zadeh (HLEQ). Data analysis was performed using SPSS software, version 25. The study findings revealed that both life therapy and acceptance and commitment therapy are effective in reducing mental pain (P < 0.001) and increasing zest for life (P < 0.001) in patients with leukemia. It can be concluded that life therapy, compared to acceptance and commitment therapy, has a greater impact on reducing mental pain and increasing zest for life in patients with leukemia. Life therapy appears to be more effective in enhancing zest for life and fostering positive emotions among these patients.